Morpho-Anatomical Traits and Soluble Sugar Concentration Largely Explain the Responses of Three Deciduous Tree Species to Progressive Water Stress - Hernandez, Jonathan O.; An, Ji Young; Combalicer, Marilyn S.; Chun, Jong-Pil; Oh, Sang-Keun; Park, Byung Bae (Frontiers in Plant Science, 2021)
Better understanding of plant drought responses is essential to improve plant water use efficiency, productivity, and resilience to ever-changing climatic conditions. Here we investigated the growth, morpho-anatomical, physiological, and biochemical responses of Quercus acutissima Carruth., Quercus serrata Murray, and Betula schmidtii Regel to progressive water-stress. Seedlings were subjected to well-watered (WW) and water-stressed (WS) conditions while regularly monitoring the soil volumetric water content, stem diameter (SD), height, biomass, stomatal conductance (gs), intercellular CO2 concentration (Ci), and leaf relative water content (RWC). We also investigated the variation in stomatal pore area (SP), specific leaf area (SLA), root xylem vessel diameter (VD), and total soluble sugar (TSS) concentration between treatments. After two months, WS significantly suppressed SD growth of Q. acutissima and B. schmidtii but had no impact on Q. serrata. Total biomass significantly declined at WS-treated seedlings in all species. WS resulted in a smaller SLA than WW in all species. The SP of WS-treated seedlings of Q. acutissima and B. schmidtii significantly decreased, whereas it increased significantly with time in Q. serrata. Larger vessels (i.e., >100 to ≤130) were more frequent at WS for Q. acutissima and B. schmidtii, whereas smaller vessels (i.e., >40 to ≤90) were more frequent at WS than at WW for Q. serrata after eight weeks. Tylosis was more frequent at WS than WW for Q. serrata and B. schmidtii at eighth week. WS seedlings showed lower gs, Ci, and RWC compared with WW-treated ones in Q. acutissima and B. schmidtii. TSS concentration was also higher at WS-treated seedlings in two Quercus species. Overall, principal component analysis (PCA) showed that SLA and SP are associated with WS seedlings of Q. serrata and B. schmidtii and the TYF, TSS, and VD are associated with WS seedlings of Q. acutissima. Therefore, water-stressed plants from all species responded positively to water stress with increasing experimental duration and stress intensity, and that is largely explained by morpho-anatomical traits and soluble sugar concentration. The present study should enhance our understanding of drought-induced tree growth and short-term tree-seedling responses to drought.